EVALUATION OF THE FAMILY HOPE PROGRAM (PKH) IN OVERCOMING POVERTY IN ERAN BATU VILLAGE BUNTU BATU SUB-DISTRICT ENREKANG DISTRICT - Citra Karisma. S; Novayanti Sopia Rukmana; Risma Niswaty (Jurnal Aktor, 2026)
This study aims to determine the evaluation of the Family Hope Program in overcoming poverty in Eran Batu Village, Buntu Batu District, Enrekang Regency and its inhibiting factors. This type of research is qualitative with data collection techniques carried out by means of observation, interviews, and documentation. The data analysis technique used consists of data reduction, data presentation and conclusion drawing. The results showed that the Evaluation of the Family Hope Program in overcoming poverty in Eran Batu Village, Buntu Subdistrict, Enrekang Regency, based on the six aspects studied, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy in general has had an impact on the recipients of this assistance, seen in each year the recipients are decreasing even though there are still some obstacles in the data collection of recipients but it is hoped that there will be an intervention between several parties not only from the village who collect data to avoid discrimination against recipients.